Efek Kombinasi Pupuk N, P, K Dan Bokashi Terhadap Pertumbuhan Dan Produksi Padi Sawah (Oryza sativa L.) - Ni Nengah Suari; Hasfiah Hasfiah (Program Studi Agroteknologi Fakultas Pertanian Universitas Dayanu Ikhsanuddin, 2021)
The rice plant (Oryza sativa L.) is one of the main food crops in Indonesia, national food needs, especially in the city of Baubau, are increasing in line with the increase in population, an effort to increase lowland rice production by using a combination of N, P, K and fertilizer. Bokashi. This study aims to determine the differences in the effect of the combination of N, P, K and Bokashi fertilizers on the growth and production of lowland rice (Oryza sativa L.). This research was conducted from February to April 2020 at the Ngkari-Ngkari Village, Bungi District, Baubau City. This study used a randomized block design (RBD) consisting of three replications. The treatment used B0 = No treatment / control, B1 = N, P, K 137,3 g + bokashi 6,250 kg plot-1, B2 = N, P, K 206,1 g + bokashi 6,250 kg plot-1, B3 = N, P, K 278,9 g + bokashi 4,68 kg plot-1, B4 = N, P, K 333,6 g + bokashi 4,68 kg plot-1, B5 = N, P, K 412,14 g + bokashi 3,125 kg plot-1 and B6 = N, P, K 518,27 g + bokashi 3,125 kg plot-1. Observable response variables include : plant height, number of tillers, number of panicles, leaf area, number of seeds per panicle, GKG productivity, net assimilation rate (LAB), and NPA (root drop ratio). Studies have shown that the high parameter of the plant, the amount and amount of paniclehave no real impact while the wide parameters of the leaf, the amount of grainby panicle, the amount of GKG productivity, the rate of net assimilation and root drop ratio have substantial impact. Treatment B6 (N, P, K 518,27 g + bokashi 3.125 kg plot-1) is the best treatment with the highest average value of productivity of GKG 5.03 tons haˉ1.